The law of mass action governs antigen-stimulated cytolytic activity of CD8+ cytotoxic T lymphocytes. - Sykulev, Y (1995)
An analysis of the initial antigen-recognition step in the destruction of target cells by CD8+ cytolytic T lymphocytes (CTLs) shows that a relationship in the form of the law of mass action can be used to describe interactions between antigen-specific receptors on T cells (TCRs) and their natural ligands on target cells (peptide-major histocompatibility protein complexes, termed pepMHC complexes), even though these reactants are confined to their respective cell membranes. For a designated level of lysis and receptor affinities below about 5 X 10(6) M-1, the product of the required number of pepMHC complexes per target cell ("epitope density") and TCR affinity for pepMHC complexes is constant; therefore, over this range TCR affinities can be predicted from epitope densities (or vice versa). At higher receptor affinities ("affinity ceiling") the epitope density required for half-maximal lysis reaches a lower limit of less than 10 complexes per target cell.